"Avtohtoni" in "neavtohtoni" Romi v Sloveniji - Janko Spreizer, Alenka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The contribution opens with the question of how is culture connected to space and which is the role played by different representatives of power with regards to the construction of Roma collectiveness in Slovenia. Based on this starting point, the article analyses the field of knowledge known as "Romology". The present analysis shows which social actors of power established the difference between those Roma who are represented as "autochtonous" and confined to one specific territories, claimed to be "autochtonous areas of settlement", and the so-called "non-autochtonous" Roma.The analysis demonstrates that the above-mentioned studies base their conclusions on the primordial and biological conceptualisations of culture, allegedly "naturally" bound to certain spaces and territories. Relying on the collected ethnography, the author crucially depicts the process, which generates the discourse of "autochtony" and "non-autochtony" in the relation between the Roma, national Romany policy, and academic tradition, which represents itself as "Romology", "Slovenian national question" or "ethnic studies."
Keywords: Slovenia; Slovenija; Romi; socialna antropologija; etnična identiteta